PENERAPAN AZAS GOOD GOVERNANCE DALAM PEMBATALAN SERTIPIKAT HAK MILIK BERDASARKAN PUTUSAN PTUN NO: 68/G/2019/PTUN-BDG - Rosadi; Endeh Suhartini; Agus Surachman (JURNAL ILMIAH LIVING LAW, 2023)
The problem that occurs is that there is a TUN Court decision which states that the authentic and strongest proof of ownership of land rights in the form of a certificate on land is canceled by a weak/underhanded proof of land ownership in the form of a letter of waiver of rights (SPH), the factor is related to BPN/Official The State Administration in issuing its products does not pay attention to AUPB / Good Gavernance then the next problem is the existence of obstacles in executing it by TUN officials and by the certificate owner by taking a silent attitude / not withdrawing the certificate which was canceled by the Court and blocking the land by the interference defendant to controlled by the plaintiff. The method used by the author uses normative legal research methods and data methods that use qualitatively the Bandung State Administrative Court decisions, etc. AUPB for TUN officials is a necessity in order to maintain the cancellation of certificates/decisions, this shows a lack of supervision to BPN TUN officials and lacks firmness in setting sanctions. Keywords : Good governance; Freehold Title; PTUN